Functional analysis of the promoter of the phase-specific WH11 gene of Candida albicans. - Srikantha, T (1995)
Candida albicans WO-1 switches spontaneously, frequently, and reversibly between a hemispherical white and a flat gray (opaque) colony-forming phenotype. This transition affects a number of morphological and physiological parameters and involves the activation and deactivation of phase-specific genes. The WH11 gene is transcribed in the white but not the opaque phase. A chimeric WH11-firefly luciferase gene containing the 5' upstream region of WH11 was demonstrated to be under phase regulation regardless of the site of integration, and a series of promoter deletion constructs was used to delineate two white-phase-specific transcription activation domains. Gel retardation experiments with the individual distal or proximal domain and white-phase or opaque-phase protein extract demonstrated the formation of one distal white-phase-specific complex and two proximal white-phase-specific complexes. Specific subfragments were tested for their ability to compete with the entire domain in the formation of complexes with white-phase protein extract in order to map the proximal domain sequence involved in white-phase-specific complex formation. Our results indicate that white-phase-specific transcription of WH11 is positively regulated by trans-acting factors interacting with two cis-acting activation sequences in the WH11 promoter.